2019
DOI: 10.1093/jas/skz140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-nitrooxypropanol on enteric methane production, rumen fermentation, and feeding behavior in beef cattle fed a high-forage or high-grain diet1

Abstract: The objective of the study was to determine whether feeding a diet supplemented with 3-nitrooxypropanol (3-NOP) affects feeding behavior altering intake and rumen fermentation. Two experiments were conducted with 9 rumen-cannulated beef steers in a replicated 3 × 3 Latin square design where animals received a high-forage or high-grain diet. Treatments were 1) a basal diet (CON), the CON diet supplemented with 3-NOP (dNOP; 100 mg/kg in dietary DM or 1 g/d), or the CON diet with 3-NOP (1 g/d) infused into the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…2019R1F1A1056904). ments methods of CH 4 emissions among all used studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 1). In short, the administration methods of NOP were direct administration via cannula, top dressed, and mixed with diet.…”
Section: Funding Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…2019R1F1A1056904). ments methods of CH 4 emissions among all used studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 1). In short, the administration methods of NOP were direct administration via cannula, top dressed, and mixed with diet.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…Several studies revealed that NOP supplementation might increase proportion of caproate when high dose of NOP supplemented [21,24], although other studies showed no sig-nificant change [15,20] or significant decrease [14]. Reynolds et al [24] reported NOP significantly increased ethanol production when was supplemented to 2,500 mg/d, and Kim et al [13] observed significant increase of lactic acid when NOP was ruminally infused in high grain diet. A few studies showed increase of several fermentation products as hydrogen sink, more evidence will be needed to understand mechanism of metabolic hydrogen produced from CH 4 reduction by NOP supplementation in rumen.…”
Section: Ruminal Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and before starting Exp. 2, the animals were used in another experiment for 4 months [11]. That study was a repeated 3 × 3 Latin square design where the animals received a high forage diet (control), a high forage diet supplemented with 3-NOP (100 mg/kg dietary DM), or the control diet with 3-NOP being infused into the rumen.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%